IMPLEMENTASI GAME BERBASIS WORDWALL DALAM PEMBELAJARAN DI SEKOLAH DASAR NEGERI 28 BANDAR BARU: Implementasi Pembelajaran dengan Game Berbasis Wordwall dalam Kegiatan Pengabdian di Sekolah Dasar Negeri 28 Bandar Baru, Kabupaten Pidie Jaya - Rambang Muharramsyah; Yuliana Yuliana; Muhibbudin Muhibbudin; Teuku Armansyah; Nadia Aldyza (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service initiative focused on implementing Wordwall-based games as an interactive learning medium at SD Negeri 28 Bandar Baru, Pidie Jaya Regency. The participants included 28 fourth-grade students and three classroom teachers who utilized these games in their instruction. By leveraging the Wordwall platform, teachers were able to create engaging and enjoyable learning activities tailored to the curriculum. The implemented methods included quizzes, matching exercises, word scrambles, and "wheel of fortune" games. The results demonstrated that the use of Wordwall-based games enhanced student learning motivation, active participation, and academic outcomes. Although challenges regarding device availability and internet connectivity arose, they were mitigated through strategies such as rotating device usage and preparing offline backup activities. Wordwall-based games have proven to be an effective interactive learning medium that fosters enjoyable and meaningful learning experiences in primary education.